Hemodynamic Functionality of Transfused Red Blood Cells in the Microcirculation of Blood Recipients - Barshtein, Gregory; Arbell, Dan; Yedgar, Saul (Frontiers in Physiology, 2018)
The primary goal of red blood cell (RBC) transfusion is to supply oxygen to tissues and organs. However, due to a growing number of studies that have reported negative transfusion outcomes, including reduced blood perfusion, there is rising concern about the risks in blood transfusion. RBC are characterized by unique flow-affecting properties, specifically adherence to blood vessel wall endothelium, cell deformability, and self-aggregability, which define their hemodynamic functionality (HF), namely their potential to affect blood circulation. The role of the HF of RBC in blood circulation, particularly the microcirculation, has been documented in numerous studies with animal models. These studies indicate that the HF of transfused RBC (TRBC) plays an important role in the transfusion outcome. However, studies with animal models must be interpreted with reservations, as animal physiology may not reflect human physiology. To test this concept in humans, we have directly examined the effect of the HF of TRBC, as expressed by their deformability and adherence to vascular endothelium, on the transfusion-induced effect on the skin blood flow and hemoglobin increment in β-thalassemia major patients. The results demonstrated, for the first time in humans, that the TRBC HF is a potent effector of the transfusion outcome, expressed by the transfusion-induced increase in the recipients' hemoglobin level, and the change in the skin blood flow, indicating a link between the microcirculation and the survival of TRBC in the recipients' vascular system. The implication of these findings for blood transfusion practice and to vascular function in blood recipients is discussed.